(untitled) (Research, Society and Development, 2019)
With the increasing number of users in the digital environment and due to the constant changes in this type of environment, the public is connecting in search of entertainment and information, but among them, companies also want to suit users and be present in this space. Thinking about how these companies act on the web when they reach their audience with online content, the objective of this research was raised, which was to identify how the tools of Digital Marketing contribute in the dissemination of the image of these stores in the city of Cajazeiras - PB. To do this, we will try to understand how these businesses carry out their Internet advertising to reach their target audience, trying to find out which Digital Marketing tools the companies have the most result, and what kind of benefits this Marketing action can bring to the company. For this, research was done on books, articles and internet on the subject, to understand the subject under study and an empirical research in the shops of the city. The results indicate that of the resources used by the companies, many make use of Digital Marketing without having a good knowledge, they can have results with the action even though it is still very little, since many need a professional that is hired to assist in various favors within company.